Mentoring and Career Development of Academics in Colleges of Education in Cross River State Nigeria - Undiyaundeye, Florence A.; Julius. A Basake (European Journal of Multidisciplinary Studies, 2017)
Currently the reasons for mentoring in our career is on the increase as the operational environment is embedded with risk , change ,staff competition, unethical career practices , high uncertainty, unfavourable government policy implementation and ignorance of the role of mentors being in control of the weak site. It is grossly required for good mentoring to be in our educational system of rewards and promotion. The study therefore investigates mentoring and career development of academia in colleges of education in Cross River state, Nigeria. A descriptive survey research design was adopted for the study. The population for the study comprised all the 1075 Chief lecturers and young lecturers ’while multi choice sampling technique was used to sample 570 respondents. One research question and two research hypotheses guided the study. The researcher developed questionnaires tagged ‘Mentoring and Career Development for Academia Questionnaire’ (MCDAQ). Questionnaire containing 12 items was the instrument for data collection, which was validated by three experts from the University of Calabar, Calabar with total reliability coefficients of 0.82. Mean ratings and standard deviation were used in answering the research questions. While T test was used in testing the hypothesis. The major findings of the study revealed that mentoring is in practices in collages of education in Cross River state, Nigeria. That there is mentoring relationships among academic staff. The study also revealed that female face more challenges in course mentoring than the male academic
Keywords: Mentoring, Career development, Career experience re- orientation, and Career openness